Perspektywa tekstowa i perspektywa kulturowa w przekładzie, czyli o kłopotach współistnienia - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2015)
On co‑existential problemes: Textual and Cultural Perspectives on Translation The process of translation assumes the existence of two separate mental spaces merging in the translator’s mind, whose freedom is limited by the responsibility towards the author and the reader, on the one hand, and, on the other, the textual imperatives manifested at the conceptual, linguistic, and stylistic levels. The transformations of strategies generating meaning during the process of translation lead to the creation of a new literary subject. The shift from the meaning of the original to the translator and the target culture does not have to imply an erasure of the source as long as it is being interpreted as a manifestation of a specific mental space. The textual perspective constitutes the foundation of translation, inasmuch as it reveals ambiguities from the point of view of the target literature and culture, and points to the necessity to resolve contextualized meanings that represent cultural differences. The encounter between two mental spaces happens due to the interpretation of the mental mechanisms that are inscribed into the text. Grammatical structures, meaning, style and literary conventions are always determined by semantic, intellectual, cultural and anthropological factors. Key words: translation, translator, freedom, responsibility, text